The effectiveness of learning media based on digital augmented reality (AR) technology on the learning outcomes of martial arts - Sonya Nelson; Resmi Darni; Fahmil Haris; Ilham Ilham; Japhet Ndayisenga; Septri Septri; Yovhandra Ockta; Dessi Novita Sari; Rifqi Festiawan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction and Objectives : The educational potential of Augmented Reality (AR) and Virtual Reality (VR) technologies has gained significant attention in recent years. Understanding teachers' willingness to adopt new technologies is crucial for supporting their integration into education. This study aims to assess the effectiveness of AR-based digital technology applications as learning media for improving martial arts learning outcomes in the Basic Engineering Materials course at the Faculty of Sports Science, Padang State University. Methodology : This experimental study used a quantitative approach. The sample consisted of 62 students from the Faculty of Sports Science, Padang State University, selected through cluster random sampling. The subjects were divided into a control group and an experimental group. Data was collected using a pretest-posttest design. Statistical analysis was performed using the Shapiro-Wilk and Wilcoxon tests in SPSS software. Results: The results showed a significant difference in learning outcomes between students using AR-based learning media and those who did not. The p-value of 0.000 (< 0.05) indicates that the use of AR-based learning media significantly improved students' learning outcomes at the Faculty of Sports Science, Padang State University. Conclusion: The study concludes that AR-based learning media are effective in enhancing students’ learning outcomes, particularly in martial arts education. This finding contributes to the development of mobile-assisted learning and technology-enhanced education. arts teaching